43⋅(x+3)+73=6

Simplify each term.

Apply the distributive property.

43x+43⋅3+73=6

Combine 43 and x.

4×3+43⋅3+73=6

Cancel the common factor of 3.

Cancel the common factor.

4×3+43⋅3+73=6

Rewrite the expression.

4×3+4+73=6

4×3+4+73=6

4×3+4+73=6

To write 4 as a fraction with a common denominator, multiply by 33.

4×3+4⋅33+73=6

Combine 4 and 33.

4×3+4⋅33+73=6

Combine the numerators over the common denominator.

4×3+4⋅3+73=6

Simplify the numerator.

Multiply 4 by 3.

4×3+12+73=6

Add 12 and 7.

4×3+193=6

4×3+193=6

4×3+193=6

Graph each side of the equation. The solution is the x-value of the point of intersection.

x=-14

Solve Graphically 4/3*(x+3)+7/3=6